**(30^2)-1 **divided by 7 gives 4 as a remainder/ It is what u r asking i suppose.

(30^2)-1 = (30+1) * (30-1) = 31 * 29 div by 7

31/7 gives 4 as a remainder ans 29/7 gives 1 as remainder

so (31*29)/7 gives 4*1 = 4 as a remainder

*(30^2)-1 *divided by 7 gives 4 as a remainder/ It is what u r asking i suppose.(30^2)-1 = (30+1) * (30-1) = 31 * 29 div by 731/7 gives 4 as a remainder ans 29/7 gives 1 as remainderso (31*29)/7 gives 4*1 = 4 as a remainder

Page 1 of 1

**(30^2)-1 **divided by 7 gives 4 as a remainder/ It is what u r asking i suppose.

(30^2)-1 = (30+1) * (30-1) = 31 * 29 div by 7

31/7 gives 4 as a remainder ans 29/7 gives 1 as remainder

so (31*29)/7 gives 4*1 = 4 as a remainder